Understanding thermostability factors of Aspergillus niger PhyA phytase: a molecular dynamics study - Noorbatcha, Ibrahim Ali; Sultan, Anas Mufid Nasri; Mohd. Salleh, Hamzah; Amid, Azura (Springer, 2013)
Abstract Molecular dynamics simulation was used to study the dynamic differences between native Aspergillus niger PhyA phytase and a mutant with 20 % greater thermostability. Atomic root mean square deviation, radius of gyration, and number of hydrogen bonds and salt bridges are examined to determine thermostability factors. The results suggest that, among secondary structure elements, loops have the most impact on the thermal stability of A. niger phytase. In addition, the location rather than the number of hydrogen bonds is found to have an important contribution to thermostability. The results also show that salt bridges may have stabilizing or destabilizing effect on the enzyme and influence its thermostability accordingly.